Genetic and biochemical characteristics in the Roma minority in the South Bohemia Region - Adámková, Věra; Hubáček, Jaroslav A; Nováková, Dita; Dolák, František; Adámek, Václav; Lánská, Věra; Tóthová, Valérie; Šedová, Lenka (Neuro endocrinology letters, 2015)
OBJECTIVE: At present, health characteristics of Roma minority within the Czech Republic are generally unknown. Therefore we examined a Roma population for some anthropometrical, biochemical and genetic parameters. DESIGN: Groups include Roma aged above 18 years (men, women), with permanent residence in the South Bohemia Region. The Roma group (302 individuals) was selected using the snowball sampling method--the same method was used to select the non-Roma control group (78 individuals) for total cholesterol and blood sugar reference values. The main non-Roma control group was selected using the quota selection method (298 individuals). All participants completed a life style questionnaire, had their body measurements taken, were weighed, had their blood pressure and heart rates measured, had a capillary blood sample taken. RESULTS: The non-Roma population had a lower Body Mass Index (BMI) (25.86 ± 4.23 vs. 27.45 ± 6.48 kg/m², p = 0.0004). The difference in BMI and weight was found to be associated with the MC4R gene. The values of systolic and diastolic blood pressure, total cholesterol, blood sugar did not differ with regard to the tested polymorphisms. We did not find any difference in the prevalence of MC4R or TMEM18 between groups. CONCLUSION: Despite educational efforts to introduce healthier life styles into the Roma population, there has been only limited success; as a result, Roma are very likely to suffer from premature complications of atherosclerotic processes, mostly due to theirs life style. Intensive further research is needed to improve the health conditions of the Roma minority, while still respecting their cultural differences.
Keywords: dospělí; Female; Minority Groups; menšiny; Adult; ženské pohlaví; Life Style; životní styl; lidé; Male; Cardiovascular Diseases; Romové; Czech Republic; index tělesné hmotnosti; kardiovaskulární nemoci; Roma; Česká republika; lidé středního věku; mužské pohlaví; Body Mass Index; Middle Aged; Humans